Louise Lightfoot and Ibetombi Devi: The Second Manipuri Dance Tour of Australia, 1957. (November 2014) - Sarwal, Amit
<x xml:space="preserve">Abstract</x> Manipur, a small state in the North-Eastern India, is traditionally regarded in the Indian classics and epics such as Ramayana and Mahabharata as the home of gandharvas (the celestial dancers). Manipuri is one of the eleven dance styles of India that have incorporated various techniques mentioned in such ancient treatises as the Natya Shastra and Bharatarnava and has been placed by Sangeet Natak Akademi within 'a common heritage' of Indian classical dance forms (shastriya nritya): Bharatanatyam, Kathak, Kathakali, Kuchipudi, Manipuri, Mohiniyattam, Odissi, Sattriya, Chhau, Gaudiya Nritya, and Thang Ta. In the late-1950s Louise Lightfoot, the 'Australian mother of Kathakali, ' visited Manipur to study and research different styles of Manipuri dance. There she met Ibetombi Devi, the daughter of a Manipuri Princess; she had started dancing at the age of four and by the age of twelve, she had become the only female dancer to perform the Meitei Pung Cholom on stage––a form of dance traditionally performed by Manipuri men accompanied by the beating of the pung (drum). In 1957, at the age of 20, Ibetombi became the first Manipuri female dancer to travel to Australia. This paper addresses Ibetombi Devi's cross-cultural dance collaboration in Australia with her impresario, Louise Lightfoot, and the impression she and her co-dancer, Ananda Shivaram, made upon audiences.